2007
DOI: 10.4049/jimmunol.179.8.5255
|View full text |Cite
|
Sign up to set email alerts
|

All-or-None Activation of CRAC Channels by Agonist Elicits Graded Responses in Populations of Mast Cells

Abstract: In nonexcitable cells, receptor stimulation evokes Ca2+ release from the endoplasmic reticulum stores followed by Ca2+ influx through store-operated Ca2+ channels in the plasma membrane. In mast cells, store-operated entry is mediated via Ca2+ release-activated Ca2+ (CRAC) channels. In this study, we find that stimulation of muscarinic receptors in cultured mast cells results in Ca2+-dependent activation of protein kinase Cα and the mitogen activated protein kinases ERK1/2 and this is required for the subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 46 publications
3
30
0
Order By: Relevance
“…Collectively, these results demonstrate that store-operated Ca 2ϩ entry is much more effective in activating cPLA 2 and LTC 4 secretion than a similar bulk cytoplasmic Ca 2ϩ elevation, establishing that the subplasmalemmal Ca 2ϩ rise is key in stimulating these enzymes. Although the present findings have utilized thapsigargin, we have previously reported that Ca 2ϩ release following activation of muscarinic receptors in RBL cells was entirely ineffective in stimulating ERK, arachidonic acid generation, and LTC 4 secretion, whereas subsequent Ca 2ϩ influx robustly activated these processes (19). Similarly, activation of FC⑀RI receptors with antigen triggered ERK activation and LTC 4 secretion through a mechanism indistinguishable from that utilized by thapsigargin (11).…”
Section: Camentioning
confidence: 57%
“…Collectively, these results demonstrate that store-operated Ca 2ϩ entry is much more effective in activating cPLA 2 and LTC 4 secretion than a similar bulk cytoplasmic Ca 2ϩ elevation, establishing that the subplasmalemmal Ca 2ϩ rise is key in stimulating these enzymes. Although the present findings have utilized thapsigargin, we have previously reported that Ca 2ϩ release following activation of muscarinic receptors in RBL cells was entirely ineffective in stimulating ERK, arachidonic acid generation, and LTC 4 secretion, whereas subsequent Ca 2ϩ influx robustly activated these processes (19). Similarly, activation of FC⑀RI receptors with antigen triggered ERK activation and LTC 4 secretion through a mechanism indistinguishable from that utilized by thapsigargin (11).…”
Section: Camentioning
confidence: 57%
“…We have previously shown that individual mast cells respond in an essentially all-or-nothing manner to agonist (15). Raising agonist concentration recruited more cells in the population, but each cell that responded did so maximally.…”
Section: Cysteinyl Leukotrienes Are Secreted At Low Levels Of Stimulumentioning
confidence: 96%
“…Early studies indicated that influx of Ca 2+ from the external medium was absolutely required for degranulation11 and that Ca 2+ oscillations generated by release of Ca 2+ from intracellular stores failed to support degranulation in antigen-stimulated RBL-2H3 cells 301. Instead, sustained Ca 2+ oscillations or global increases of [Ca 2+ ] i maintained by Ca 2+ influx did support degranulation 309,320. A similar tight dependency on Ca 2+ influx was noted for the recruitment of protein kinase C and components of the ERK/PLA 2 /5-lipoxygenase pathway in RBL cells activated with thapsigargin309 or receptor agonists 320.…”
Section: Additional Details Of Calcium Signaling In Mast Cellsmentioning
confidence: 99%
“…Instead, sustained Ca 2+ oscillations or global increases of [Ca 2+ ] i maintained by Ca 2+ influx did support degranulation 309,320. A similar tight dependency on Ca 2+ influx was noted for the recruitment of protein kinase C and components of the ERK/PLA 2 /5-lipoxygenase pathway in RBL cells activated with thapsigargin309 or receptor agonists 320. Some mast cell stimulants such as agonists of the adenosine A 3 receptor321 and purinergic P2Y receptor320 elicit transient production of IP3 and release of stored Ca 2+ without activating influx mechanisms, Ca 2+ -dependent signals, and degranulation.…”
Section: Additional Details Of Calcium Signaling In Mast Cellsmentioning
confidence: 99%